Modelling and testing the effects of space radiation on space-borne electronic components - Snell, Holly (Department of Electrical Engineering, 2018)
Outer space is a hazardous environment for satellites as they are continuously exposed to harsh space radiation in the form of cosmic rays and high-energy electrically charged particles (protons, electrons and alpha particles). Mission-critical electronic components are especially susceptible to space radiation as high-velocity charged particle impacts on molecular-sized circuitry can cause significant device upsets or permanent damage, compromising a satellite's functional integrity. In order to mitigate this radiation hazard, electronic components are carefully selected and tested prior to deployment. Part of this process involves consulting a space radiation model in order to be able to estimate the type of radiation environment the electronics will be exposed to. There are many different environmental models to choose from and the output from the models will influence whether a certain device will be selected or not. Due to this, the model selection process should be very well understood and all parameters carefully chosen. This project aims to describe the radiation environment in low Earth orbit, and to provide guidelines for using the space radiation models found on the Space ENVironment Information System (SPENVIS). By going through the modelling process in detail, we have found that the trapped radiation models are completely independent of the date specified when describing the orbit of interest. We found that all long-term solar proton models (except King) assume a zero flux for solar minimum dates. The accuracy of the model output for a specific orbit depends on the duration of the model's time span. For instance, we found that for certain low Earth orbits, the accuracy of the model output could be easily improved by increasing the number of days in the orbit generator from one to three. For the low Earth orbits we selected to analyse, we found that a one-year mission delay at any point on the solar cycle will not have great enough an effect on the output to warrant a re-calculation. It is important to consider both trapped and non-trapped radiation when calculating an upset rate and, lastly, the upset rate calculation could be altered by a factor of 1000 simply by selecting different models for the exact same device and orbit. We conclude this study with some guidelines for the use of SPENVIS for radiation modelling during mission planning.